The Entropy of a Natural Number - Minculeta, N.; Pozna, C. (Acta Technica Jaurinensis, 2011)
The aim of this paper is to introduce the concept of the entropy of a natural number. This new concept is the synthesis of the entropy and of the prime numbers concepts. The natural number structure is represented by its factorization in prime numbers. The entropy gives us the possibility to analyze the order of this structure. Using the natural number entropy concept has reviled interesting results concerning the internal structure of a natural number.